2014
DOI: 10.5152/tftrd.2014.31643
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Laser and Extracorporeal Shock Wave Therapies in Treatment of Lateral Epicondylitis

Abstract: Objective: Lateral epicondylitis (LE) is a common painful problem of the elbow. This study was conducted to evaluate and compare the effectiveness of extracorporeal shock wave therapy (ESWT) and lowintensity laser therapy in LE treatment. Material and Methods: The study included 60 LE patients. Subjects were divided into two groups randomly. Group 1 received ESWT, while group 2 received laser therapy. Presence of lateral epicondyle tenderness, elbow pain, and hand grip strength (HGS) were evaluated at the begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
1
20
0
3
Order By: Relevance
“…Therefore, ESWT may be a good choice for tennis elbow when conventional treatments are ineffective. Similarly, Devrimsel et al [28] reported that ESWT was significantly better than laser therapy for LE treatment, and Vulpiani et al [34] found that ESWT was superior to cryoultrasound at 6 months and 1 year posttreatment according to VAS scores and patient satisfaction ratings.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, ESWT may be a good choice for tennis elbow when conventional treatments are ineffective. Similarly, Devrimsel et al [28] reported that ESWT was significantly better than laser therapy for LE treatment, and Vulpiani et al [34] found that ESWT was superior to cryoultrasound at 6 months and 1 year posttreatment according to VAS scores and patient satisfaction ratings.…”
Section: Discussionmentioning
confidence: 95%
“…Of the included studies, one investigated ( n = 1) Achilles Tendinopathy (AT) [ 53 ]; one investigated De Quervain’s Tenosynovitis (DQT) ( n = 1) [ 51 ]; seven ( n = 7) investigated Lateral Elbow Tendinopathy (LET) [ 36 , 43 , 45 , 46 , 48 , 50 , 52 ]; one ( n = 1) investigated Patella Tendinopathy (PT) [ 38 ]; and seven ( n = 7) investigated Sub-acromial Syndrome/Rotator Cuff Tendinopathy (SAS/RT) [ 37 , 42 , 44 , 47 , 49 , 54 , 55 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four weeks; 3. Three month follow up Devrimsel 2014 [ 46 ] LET 60; 30/30 PBM; ESWT VAS Four weeks 1. Baseline; 2.…”
Section: Resultsmentioning
confidence: 99%
“…[31] ESWT'nin lokal steroid enjeksiyonu kadar etkili olduğunu ileri sürerken, Devrimsel ve ark. [32] ESWT'nin lazer tedavisine kıyasla daha etkili olduğunu bildirmişlerdir. Buna karşın Buchbinder ve ark.nın [33] 2005 yılında yayınla-dıkları derlemede, lateral epikondilitli 1006 hastanın değerlendirildiği plasebo kontrollü dokuz çalışmada, ESWT'nin ağrı ve dirsek fonksiyonlarına çok az katkı sağladığı veya hiç etkisi olmadığını, 93 olguluk bir çalışmada ise steroid enjeksiyonunun ESWT'den daha etkili olduğunu bildirmişlerdir.…”
Section: Discussionunclassified